2020
DOI: 10.2147/dddt.s231293
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of Fimasartan versus Valsartan and Olmesartan on Office and Ambulatory Blood Pressure in Korean Patients with Mild-to-Moderate Essential Hypertension: A Randomized, Double-Blind, Active Control, Three-Parallel Group, Forced Titration, Multicenter, Phase IV Study (Fimasartan Achieving Systolic Blood Pressure Target (FAST) Study)</p>

Abstract: Purpose: Head-to-head comparison of the blood pressure (BP) lowering effect of fimasartan versus valsartan, with olmesartan as a reference, on office blood pressure and ambulatory BP. Patients and Methods: Of the 369 randomly assigned patients in this study, 365 hypertensive patients were referred as the full analysis set and divided into 3 groups with a 3:3:1 ratio (fimasartan group: 155, valsartan group: 157, olmesartan group: 53). After the 2-week single-blind placebo run-in period, initial standard doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“… 32 , 33 Many head‐to‐head studies have revealed more potent antihypertensive effects, particularly when compared with losartan or valsartan. 22 , 34 , 35 However, these newer ARBs do not have compelling evidence of long‐term cardiovascular outcomes, and the clinical use of these drugs is limited. Our study demonstrates that newer ARBs have similar long‐term clinical outcomes to those of earlier ARBs, based on the data of many patients in the real world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 , 33 Many head‐to‐head studies have revealed more potent antihypertensive effects, particularly when compared with losartan or valsartan. 22 , 34 , 35 However, these newer ARBs do not have compelling evidence of long‐term cardiovascular outcomes, and the clinical use of these drugs is limited. Our study demonstrates that newer ARBs have similar long‐term clinical outcomes to those of earlier ARBs, based on the data of many patients in the real world.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Several studies comparing the antihypertensive effect of ARBs have shown differences in the magnitude of BP reduction. 34 , 35 This difference in BP control may affect patients' prognoses. In patients with acute myocardial infarction, comparative analysis revealed that insurmountable ARBs, which have a longer and more stable duration of action, were more effective on long‐term clinical outcomes compared with surmountable ARBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Fimasartan is mainly excreted unchanged through bile by multiple cytochrome p450s, mainly CYP3A, and less than 3% is excreted in urine. Fimasartan has excellent efficacy in controlling hypertension, 8 but the pharmacokinetics of the drug have raised concerns regarding the increased possibility of drug-induced liver injury (DILI). To date, few case reports have described ARB-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…9 10 11 12 Most cohort studies have not reported detailed liver injury incidence and outcomes related to ARB-related DILI, instead only the overall, severe adverse drug-related reaction rates have been reported. 8 …”
Section: Introductionmentioning
confidence: 99%